Targeting gut microbiota to regulate the adaptive immune response in atherosclerosis - Giakomidi, Despina; Ishola, Ayoola; Nus, Meritxell (Frontiers in Cardiovascular Medicine, 2025)
Atherosclerosis, the leading cause of death worldwide, is a chronic inflammatory disease leading to the accumulation of lipid-rich plaques in the intima of large and medium-sized arteries. Accumulating evidence indicates the important regulatory role of the adaptive immune system in atherosclerosis during all stages of the disease. The gut microbiome has also become a key regulator of atherosclerosis and immunomodulation. Whilst existing research extensively explores the impact of the microbiome on the innate immune system, only a handful of studies have explored the regulatory capacity of the microbiome on the adaptive immune system to modulate atherogenesis. Building on these concepts and the pitfalls on the gut microbiota and adaptive immune response interaction, this review explores potential strategies to therapeutically target the microbiome, including the use of prebiotics and vaccinations, which could influence the adaptive immune response and consequently plaque composition and development.